2014
DOI: 10.3109/01443615.2014.990431
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery ligation at the beginning of total laparoscopic hysterectomy reduces total blood loss and operation duration

Abstract: The purpose of this study was to compare the feasibility, blood loss, duration of surgery and complications between patients in whom both uterine arteries were ligated by surgical clips and cut using a 5-mm ligature at the beginning of total laparoscopic hysterectomy (TLH) and patients in whom uterine arteries were not ligated at the beginning of TLH. In our prospective study, a total of 60 women underwent TLH. Uterine artery ligation (UAL) was done at the beginning of the procedure. Women were divided into TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 12 publications
1
24
1
3
Order By: Relevance
“…as a technique to control blood loss and protect the ureter, even in cases with large uteri. The RPD required for this technique may also help prevent other visceral injuries by allowing full visualization and lateralization of the ureters . A randomized study of 400 patients showed shorter operative time (OT) and significantly less blood loss in patients who underwent uterine artery ligation at the origin versus the isthmo‐cervical region …”
Section: Methodsmentioning
confidence: 99%
“…as a technique to control blood loss and protect the ureter, even in cases with large uteri. The RPD required for this technique may also help prevent other visceral injuries by allowing full visualization and lateralization of the ureters . A randomized study of 400 patients showed shorter operative time (OT) and significantly less blood loss in patients who underwent uterine artery ligation at the origin versus the isthmo‐cervical region …”
Section: Methodsmentioning
confidence: 99%
“…Many previous studies have shown that clamping the uterine arteries during laparoscopic hysterectomy results in less blood loss. [16] In one study, total blood loss in early uterine artery ligation group was found to be 10 ml less than that of the Standard-TLH group (50 vs. 60 ml). [17] The second advantage is that the location where the ureter crosses the uterine artery is clearly visible in the skeleton uterus technique.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, the suture ligation method in TLH may involve a prolonged surgical time because it requires a learning curve. The skill of an advanced surgeon compensates for the suture method and operation time of TLH [ 13 14 15 ]. In this study, the mean operation time was 96.9 minutes.…”
Section: Discussionmentioning
confidence: 99%